IMPLEMENTATION OF SCIENTIFIC READING BASED PROJECT (SRBP) MODEL TO IMPROVE COOPERATION AND NATURAL SCIENCE LEARNING OUTCOMES ABOUT HEAT TRANSFER FOR FIFTH GRADE STUDENTS OF SDN KEMIRI IN ACADEMIC YEAR OF 2019/2020 - Ellie Syafitri; Tri Saptuti Susiani; Kartika Chrysti Suryandari (Universitas Sebelas Maret, 2021)
The study aimed to improve cooperation and learning outcomes of fifth grade students of SD N Kemiri in academic year of 2019/2020.It was classroom action research conducted in two cycles. The subjects were fifth grade students of SD N Kemiri. Data collection techniques were tests and non-tests. The data validity used technique triangulation and source triangulation. Data analysis included data reduction, data presentation, and conclusions drawing.The results showed that the Scientific Reading Based Project improved cooperation and student learning outcomes. Thecooperation improved because the students were confident to deliver their opinion, the students helped their friends finding difficulty, and the students had self-control for not interrupting discussion and cooperation. The learning outcomes improved because the students mastered about heat transfer and answered the cognitive question correctly in the level of C1-C4. It concludes that the implementation of Scientific Reading Based Project model improves cooperation and learning outcomes for fifth grade students of SD N Kemiri in academic year of 2019/2020.